KONSEP PANCA OPAT MASYARAKAT ADAT KASEPUHAN CIPTAGELAR DALAM PERSPEKTIF DESIGN THINKING - Isfiaty, Tiara (Narada : Jurnal Desain dan Seni, 2024)
This study aims to identify the concept of Panca as an invention rooted in the indigenous Kasepuhan Ciptagelar community's local wisdom as a way to improve their lives while upholding the honorable principles of their customs. Innovation is a practice of human intelligence by utilizing technology to solve life problems from time to time. This fact is in line with design science as a problem solver in order to improve human life for the problems they face. Problem-solving activities in design can be studied using a design thinking approach. The cultural practices of the Kasepuhan Ciptagelar indigenous community are a form of innovation based on local wisdom that teaches us about overcoming problems that occur in the internal environment in a way that they create themselves. One of them is known as the Panca Opat concept. For the community, Panca Opat is a concept that is the basis for the customary order of their lives. The area of this research is the science of fine arts and design. This study uses a design thinking approach. The cultural practices of the Kasepuhan Ciptagelar indigenous community are a form of innovation based on local wisdom that teaches us about overcoming problems that occur in the internal environment in a way that they create themselves. One of them is known as the Panca Opat concept. For the community, Panca Opat is a concept that is the basis for the customary order of their lives. The area of this research is the science of fine arts and design. This research uses a design thinking approach. The stages analyzed are three stages, namely the stage of identifying problems (Empathize stage), the stage of solving problems based on the user's perspective (Define stage) and the stage of answering problems including the use of technology (Ideate stage). At the Empathize stage, the nature is to identify problems so that the research model that will be carried out is qualitative research. Qualitative methods refer to Moleong (1993), described as research that intends to understand the phenomenon of what is experienced by research subjects such as behavior, perception, motivation, actions holistically, and by means of description in the form of words and language. The results of the study are the findings of parako as a representation of the concept of panca opat. Parako is a crucial and constructive finding in the visual culture of the archipelago.